Single-cell analysis reveals lasting immunological consequences of influenza infection and respiratory immunization in the pig lung - Muir, Andrew; Paudyal, Basudev; Schmidt, Selma; Sedaghat-Rostami, Ehsan; Chakravarti, Soumendu; Villanueva-Hernández, Sonia; Moffat, Katy; Polo, Noemi; Angelopoulos, Nicos; Schmidt, Anna; Tenbusch, Matthias; Freimanis, Graham; et al. (PLoS Pathogens, 2024)
The pig is a natural host for influenza viruses and integrally involved in virus evolution through interspecies transmissions between humans and swine. Swine have many physiological, anatomical, and immunological similarities to humans, and are an excellent model for human influenza. Here, we employed single cell RNA-sequencing (scRNA-seq) and flow cytometry to characterize the major leukocyte subsets in bronchoalveolar lavage (BAL), twenty-one days after H1N1pdm09 infection or respiratory immunization with an adenoviral vector vaccine expressing hemagglutinin and nucleoprotein with or without IL-1β. Mapping scRNA-seq clusters from BAL onto those previously described in peripheral blood facilitated annotation and highlighted differences between tissue resident and circulating immune cells. ScRNAseq data and functional assays revealed lasting impacts of immune challenge on BAL populations. First, mucosal administration of IL-1β reduced the number of functionally active Treg cells. Second, influenza infection upregulated IFI6 in BAL cells and decreased their susceptibility to virus replication in vitro. Our data provide a reference map of porcine BAL cells and reveal lasting immunological consequences of influenza infection and respiratory immunization in a highly relevant large animal model for respiratory virus infection.
CRIS-Team Scopus Importer:2024-07-26